“They sent me home to die” – occupational diseases and the gold mining industry in post-apartheid South Africa - Potgieter, Cathy-Ann (Department of Political Studies, 2023)
In 2016 a class action suit was certified in the case of Nkala & Others v Harmony Gold Mining Company Limited & Others (2016). The action was instituted by representatives of thousands of current and former miners from Southern African countries. Their intent was to claim damages from mining companies for causing their contraction of silicosis and/or tuberculosis as a result of poor working conditions. Before the Court could make any pronouncement on liability, the parties reached an agreement out of court whereby the mining companies set up the Tshiamiso Trust to provide for compensation. This thesis contextualises the Nkala case in post-apartheid South Africa, where economic inequalities have intensified despite the constitutional transition. Where the law was used in the past to support injustice, the intention of law-making after the transition was to create a new framework that sought to protect human rights, including socio-economic rights. The extent to which it is able to effect justice to those most profoundly impacted by apartheid policies falls under scrutiny in the face of prevailing inequality, especially in the context of mining labour relations. This thesis therefore questions whether this new framework has been able to deliver the promise of justice for miners who find themselves located within a context of over a century of racialised labour exploitation and extremely hazardous working conditions. That the applicants in the Nkala case had to resort to the common law to vindicate their rights to adequate compensation despite the existence of legislation that purports to provide for this calls into question the practical efficacy of such rights-based legislation. Where the Court in the Nkala case acknowledged the inadequacy of the legislative mechanism for occupational disease and injury, the potential of the Trust in providing for meaningful compensation must fall under scrutiny. The role that compensation plays in the broader context of remedial justice will therefore be analysed to consider where the outcome of the Nkala case may fall short in addressing the structural injustices caused by the mining industry.